Community Participation on Pilkada of Mandailing Natal Regency in Panyabungan District, 2020 (Study of Political Communication) - Nurhikma Hayati; Indah Anjar Reski; Robby Maulidi Arif (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The study discussed about Community Participation on Pilkada of Mandailing Natal Regency in Panyabungan District, 2020. This study use descriptive qualitative research. The result in study show that the election message conveyed by the Madina KPU involved a reference group, namely groups that have a big influence in determining good and correct elections, call them religious leaders, the existence of these religious leaders can remind the public to choose leaders according to their religion, choose leaders consciously and avoid the name money politics, as well as traditional leaders, there are traditional leaders or community leaders. All of them have an important role in the success of the Pilkada and invite the public to participate and be willing to cast their votes in the elections held by the KPU in 2020.